Israel Ramírez Cruz e Yliana Rodríguez González (eds.), Los raros. Autores y géneros excluidos en la literatura hispánica. El Colegio de San Luis, San Luis Potosí; 379 pp. - Villarruel, Antonio (El Colegio de México, 2023)
Israel Ramírez Cruz e Yliana Rodríguez González (eds.), Los raros. Autores y géneros excluidos en la literatura hispánica. El Colegio de San Luis, San Luis Potosí; 379 pp.